Feasibility study of IPTV video-on-demand system with setbox-participated P2P distribution - Xiu-yan JIANG; Yin-shu PU; Yuan LIU; Xin LIU; De-jian YE (Tongxin xuebao, 2012)
In order to reduce the operation and deployment cost of Shanghai Telecom IPTV system,the IPTV VOD scheme with setbox-participated P2P distribution may be feasible.To study the feasibility of this scheme,firstly the primary performance indicator and primary related parameters to evaluate the scheme were proposed;then the actual user behaviors and the real topology of Shanghai Telecom IPTV system were analyzed,a large-scale IPTV simulation system RVSPS was built and this system was stimulated with real topology and actual user behaviors;after that the impact that various parameters have on the primary performance indicator was analyzed;and finally a detailed feasibility was given that study of IPTV VOD scheme with setbox-participated P2P distribution from a technical perspective.